(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Perception is an important component in the process of understanding students. Students’ misperceptions in translating a mathematical concept result in errors in problem solving. The purpose of this study was to determine the effect of visual perception on student mathematics learning outcomes. The method used in this research is observation of student work and interviews. The results of this study indicate that students who are still weak in visual perception have difficulty working on mathematical problems. In conclusion, visual perception has an influence on students’ mathematics learning outcomes.